PERFORMANCE EVALUATION OF MAGNUS SCREW PRESS (MODEL MS-100) FOR PALM KERNEL OIL EXTRACTION (Nigerian Journal of Technology, 2017)
The screw (expeller) press is extensively used for commercial extraction of palm kernel oil (PKO) from oil-palm kernels. In this work, Magnus (Nig.)screw press (Model MS-100,) locally fabricated at Nsukka, Nigeria was evaluated for throughput capacity, feed rate, press cake oil content, oil expelling efficiency (OEE), percentage un-pressed grits output, percentage sludge output, and specific energy consumption. One-factor-at-a-time (OFAT), completely randomized designed (CRD) experimental approach with 4 factor levels and 2 replications was used to determine the effect of kernel moisture contents (KMC), kernel heating temperatures (KHTs), and kernel heating durations (KHDs) on the (OEE) of the screw press. Analysis of variance (ANOVA) technique was used to analyze the results. In its best operating settings, the MS-100 screw press has a throughput capacity of 91.7 kg-products/h at an average feed rate of 101.7 kg-kernels/h, press cake oil content of 13.6% (w/w); percentage actual oil yield of 33.6% (w/w); percentage cake output of 38% (w/w); percentage un-pressed kernel grits output  of 14.2% (w/w); percentage sludge output of 3.6% (w/w); OEE of 73%; and specific energy consumption of 0.44 kWh/kg-kernels. The screw press is adjudged suitable for palm kernel oil extraction based on its OEE. The ANOVA of the results show that the best kernel factors for highest OEE include KMC of 5% w.b.; KHT of 50 - 130o C; and KHDs of 5 - 10 min. The 14.2% un-pressed kernel grits output, however, is a problem of Magnus Screw Press that needed to be reduced or eliminated through design modifications.http://dx.doi.org/10.4314/njt.v36i2.40